Coalition of Zeidiyeh and Abbasid in the First Phase of Abbasid Era; Grounds, Elements and Consequences - Hossein Hosseiniyan Moqadam; Ruhollah Tohidiniya (تاریخ اسلام)
The propagation of the thoughts of Zeid Ibn e- Ali 122 A.D and Zeidiyan supporting the leaders of Hassani changed Zeidiyeh to an effective sect in various domains. On the other hand, the first Abbasid caliphs took advantage of any strategies to bring the Shiite uprisings to an end and achieve an everlasting authority. One of the main strategies of Abbasid caliphs has been the penetration among Shiite groups. The main issue of the present article is the answer to this question pertaining to the existence of coalition between Abbasid and Zeidiyan in the first phase of Abbasid era. The study of the interactions of these two groups demonstrates the existence of a current attributed to the weak people some beliefs of them such as the allowance of granted Imamate that would depreciate their thought borderline with Abbasid caliphs. The article concludes that Abbasid caliphs could apparently achieve alliance with Zeidiyan besides having effect on them via taking advantage of the existent grounds.